(untitled) (Research, Society and Development, 2021)
Low back pain is a pathology that affects several groups of workers worldwide, being one of the most common musculoskeletal disorders today. It can interfere with the biomechanics of the entire spinal segment, leading to movement restriction and decreased muscle strength, which reflects on absences from work and, consequently, on the quality of life of these individuals. This study sought to analyze the profile of the incidence of low back pain among Physiotherapists working in Santarém - PA. The sample consisted of 21 physical therapists and, for data collection, an online form based on existing questionnaires was used, namely: Oswestry, Macnab Criterion, Roland Morris and Nordic Questionnaire, associated with the VAS scale. The data obtained were through quantitative descriptive statistics. It was found in the research the presence of a high rate of pain, numbness and discomfort in the lumbar region. The sample had an average age of 29 years, and females had a higher rate, and according to Farinha et al. (2013), the average age was between 26 and 30 years old. Despite a higher rate reported by participants in the last 12 months, they reported that these pains do not interfere with their normal work activities. And, in general, the pain reported by the VAS scale was moderate. Given the size of the data found, it was found that more research related to this theme is carried out to deepen the study in the area.